Seroprevalence Of Dengue Infection In A Tertiary Care Hospital From Southern Rajasthan - Soni, Rahul; Bhatnagar, Ritu (Journal of Neonatal Surgery, 2025)
Introduction: Dengue continues to be a significant vector-borne viral infection in tropical and subtropical regions, accounting for considerable morbidity and mortality. With repeated outbreaks in India, particularly among males and young adults, prompt diagnosis and surveillance are vital. Materials & Methods: A hospital-based cross-sectional study was conducted at Pacific Medical College and Hospital, Udaipur, from April 2023 to March 2024. Febrile patients (n = 2315) had 3–5 mL of blood drawn. Serum was analyzed using rapid SD BIOLINE immunochromatographic assays for dengue NS1 antigen and IgM/IgG antibodies. Data were entered into Microsoft Excel and reported using descriptive statistics. Results: Of the total samples, 260 (11.23%) were seropositive. Among these, 143 (55%) were male and 117 (45%) female. Age distribution indicated that the majority were 21–30 years (65; 25%), followed by 11–20 years (54; 20.8%). Serological results: NS1 antigen only in 110 (42.4%), IgM only in 108 (41.5%), IgG only in 5 (1.9%), NS1 + IgM in 25 (9.6%), NS1 + IgG in 2 (0.8%), IgM + IgG in 5 (1.9%), and NS1 + IgM + IgG in 5 (1.9%). Conclusions: The 11.23% seroprevalence underscores dengue’s public health impact in Central India, disproportionately affecting males and young adults. Deployment of NS1- and IgM-based rapid diagnostics is crucial for early case identification. Continued seroepidemiological surveillance and vector control measures are warranted to mitigate dengue-related morbidity and mortality